A non-instrumental method to determine hydraulic heads on low-lying coastal aquifer - Kassim, Mohd. Azraai; Hanapi, Muhammad Nassir; Abdullah, Mohd. Harun (Faculty of Civil Engineering, UTM, 2000)
The technique introduced in this paper is to provide an alternative method to determine hydraulic heads in an unconfined coastal aquifer. The heads could be established within a study area without the needs to use any instrument, such as a theodolite. Instead, a less costly small-diameter transparent tube is used to produce a horizontal plane, formed by a balanced water level in it. Such planes are used as reference levels between two wells on an area, which is relatively flat. Current tidal heights are required in order to calibrate the measurements obtained from the reference levels to the mean sea level. The application of this method at field as a case study has revealed the reduction and critical condition of h in the phreatic aquifer of a small island, due to the frequent pumping of the wells.